Building Human Capital in Tourism and Hospitality: Perspectives from theory and practice - Marques, Jorge (2025)
Career development in the tourism and hospitality industry has attracted greater attention, leading to a higher recognition of the relevance of formal and industry-specific education and training. New career opportunities emerge as new challenges arise, urging for ongoing and renewed debates surrounding higher-level skills and the development and optimization of human capital. Building bridges between higher education institutions, the industry, and other relevant stakeholders - primarily via needs assessment, curriculum design, and monitoring of on-the-job training practices and processes - is critical to promoting the employability of a graduate-level skilled workforce.